On certain resolvent convergence of one non-local problem to a problem with spectral parameter in boundary condition - Cheremnikh, E. V. (Methods of Functional Analysis and Topology, 2008)
A family of non-local problems with the same finite point spectrum is given. The resolvent convergence on a dense linear subspace which gives a problem with spectral parameter in the boundary condition is considered. The spectral eigenvalue decomposition of the last problem on the half line for Sturm-Liouville operator with trivial potential is given.